Innovation in cultural diplomacy: the case of China - Zhiyan Guo (2022)
This study focuses on the innovation of China’s cultural diplomacy (CCD) by means of the Confucius Institute (CI). The main contents revolve around the following research goals: 1) to understand the strategic framework and practical path of CCD, and to clarify the context of its inheritance and innovation; 2) to analyze whether the CI, epitomized as a crucial innovation of CCD, has improved China’s national image in Portuguese-speaking countries (PSCs) and enhanced the attraction and international competitiveness of Chinese culture; and 3) to explore how China can better formulate its CD strategy in line with the exigencies of the modern era. The study combines the methods of literature review, case study, and questionnaire research to explore the topics from different perspectives to strengthen the scientific nature of the research results. In addition to the introduction and conclusion, the thesis is divided into five chapters. Chapter 1 discusses the connotation and value of CD. Chapter 2 expounds the development and innovation of CCD. Chapter 3 systematically summarizes China’s cultural interaction in its diplomatic process with PSCs. Chapter 4 elaborates on the CI in terms of its operation mode and diplomatic means. Chapter 5 forms the core of the study and involves empirical analysis of case-study and questionnaire data. It aims to investigate the functions, public image, influence, and practical means of CIs in the process of CD. Major findings indicate that CIs in PSCs have achieved ideal social feedback and play a positive role in shaping the image of China. However, according to the different continents where CIs are located, the survey results show distinct characteristics which are closely related to China’s different foreign policies towards Latin America, Europe, and Africa and are determined by the historical experiences and national conditions of the various countries. The future task for CCD is to clarify China’s institutional roots and the cultural genes behind its development by using cultural exchanges and China’s fluid culture to convey a message of China’s pursuit of peace, development, and cooperation.